Dinamika Budaya dan Ekonomi dalam Perawatan Lansia Ketergantungan pada Masyarakat Minangkabau - Tresno, Tresno; Rifai, Muhammad; Hapsari , Yuanita Dwi; Kurniawan, Deni Aries; Oktanedi, Aldri (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2025)
The Indonesian government has developed an elderly care program through Posyandu Lansia, a community-based health service at the lowest administrative level. However, this program tends to overlook the cultural and economic dynamics that influence medical treatment for dependent elderly individuals. This article examines the relationship between culture and economy in the medical treatment choices of dependent elderly individuals. The research employs an ethnographic method, collecting data through observations, in-depth interviews, kinship diagrams, and life history analysis. Informants were selected using purposive sampling, consisting of dependent elderly individuals and informal caregivers. The data were analyzed descriptively through case studies of dependent elderly individuals. The findings reveal that elderly medical treatment is carried out simultaneously through both traditional and modern medicine. Dependent elderly individuals are often labeled as suffering from sakit tuo (old-age illness). This term has dual meanings: it refers both to the socioeconomic condition of the elderly, who are no longer able to engage in social and economic activities and therefore require family care, and to the physical and psychological health deterioration that occurs with aging, which is treated using both traditional and modern medicine. Economically disadvantaged dependent elderly individuals can only access medical treatment from midwives and community health centers puskesmas, as these services are relatively low-cost. In contrast, wealthier elderly individuals can afford private medical practitioners and hospital treatment. This disparity makes impoverished elderly individuals more vulnerable in receiving adequate care in the future.